2020
DOI: 10.1177/0020764020920918
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a mental health promotion program on Korean firefighters

Abstract: Background: There is worldwide interest in the mental health of firefighters, since they are more prone to exposure to traumatic stress and psychiatric disorders. Aims: This study aimed to assess their mental health and provide individualized support to local firefighters through a mental health promotion program. Method: Eighteen hundred and fifty-nine active Korean firefighters in 2015 and 2017 (502 and 1,357, respectively) participated in the ‘Visiting Counselling Centre for Firefighters’ program commission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…Two studies found a reduction in depression symptoms and suicidal ideation following intervention implementation, both conducted in Asia [ 25 , 54 ], although there was no significant reduction of depression as assessed by the Hamilton Depression Scale [ 25 ]. Of these, one also found reductions in agitation and guilt [ 25 ] and the other in anxiety, insomnia and alcohol use [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found a reduction in depression symptoms and suicidal ideation following intervention implementation, both conducted in Asia [ 25 , 54 ], although there was no significant reduction of depression as assessed by the Hamilton Depression Scale [ 25 ]. Of these, one also found reductions in agitation and guilt [ 25 ] and the other in anxiety, insomnia and alcohol use [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, the number of consulting experts was too small compared to the number of firefighters, and special intervention programs were limited. In Korea, very few psychological counselors belong to the National Fire Agency, and this majorly involves employing external professional psychological counselors [25]. As a result, the program quality ends up being poor, and it inevitably becomes a formal consultation.…”
Section: Discussionmentioning
confidence: 99%
“…En el artículo de Smith, TD et al, también se recomienda realizar valoración periódica de estrés y burnout en esta población, dado que estas situaciones tuvieron asociación con prácticas laborales inseguras, y comportamiento ciudadano de seguridad o comportamiento del equipo de protección personal disminuido (23). Otro estudio realizado por Won, GH et al, analizando bomberos de corea del sur presenta evidencia apoyando fuertemente la implementación de estos programas de salud mental, dado que se determinó que, estableciendo programas, ofreciendo tamizaje para condiciones de salud mental y consejería individual y grupal mejora los síntomas de psicopatología (24) Consideramos relevante tener en cuenta como subpoblación de riesgo a las mujeres en los cuerpos de bomberos. Se evidencio que a pesar de encontrarse expuestas a los mismos eventos potencialmente estresores este grupo por ser una minoría dentro de los cuerpos de bomberos también esta expuesto a otras situaciones estresoras como la discriminación de genero y la dificultad para mantener un balance entre los roles de genero y su profesión.…”
Section: Salud Mentalunclassified
“…Los estudios de salud mental analizados evidencian como las situaciones de estrés laboral, burnout y la exposición a eventos potencialmente traumáticos se asocia con el desarrollo de condiciones de salud mental en los bomberos, entre estas se destaca el trastorno de estrés postraumático, la depresión, la ansiedad, insomnio y consumo de sustancias psicoactivas (20,23,24,29). A su vez se reconoce que estas condiciones en el ámbito de la salud mental tienen un impacto en el desempeño y seguridad laboral (23).…”
Section: Salud Mentalunclassified